Implementasi model pembelajaran Project Based Learning (PjBL) dalam materi teks ulasan di kelas VIII SMP Negeri 22 Kota Jambi - Citra, Citra; D, Yusra; Yusra, Hilman (Aksara: Jurnal Bahasa dan Sastra, 2023)
This study aims to describe the implementation of the Project Based Learning (PjBL) learning model in review text material for class VIII SMP Negeri 22 Jambi City. The subjects of this study were Indonesian language teachers and eighth grade students at SMP Negeri 22 Jambi City. The approach used in this study is a qualitative approach. The type of research used in this research is phenomenology. The data obtained from this study are in the form of observations and results of interviews carrying out the learning process in the implementation of the Project Based Learning (PjBL) learning model in review text material for class VIII SMP Negeri 22 Jambi City starting from the initial activities, core activities and closing activities. The results of this study indicate that the implementation of the Project Based Learning (PjBL) learning model in class VIII review text material at SMP Negeri 22 Jambi City has been running according to the PjBL steps proposed by Widiarso, E (2016: 184), namely: (1) determination of questions fundamentals, (2) designing project plans, (3) compiling schedules, (4) monitoring students and project progress, (5) testing results, and (6) evaluating experiences. Project Based Learning facilitates discussions between students who exchange ideas to complete their projects. Teachers have been able to apply PjBL in writing review texts properly and correctly.Keywords: project based learning, writing, review text